Evaluation of forest decontamination using radiometric measurements. (November 2016) - Cresswell, Alan J.; Kato, Hiroaki; Onda, Yuichi; Nanba, Kenji
Abstract: An experiment has been conducted to evaluate the additional dose reduction by clear felling contaminated forestry in Fukushima Prefecture, Japan, and using the timber to cover the areas with wood chips. A portable gamma spectrometry system, comprising a backpack containing a 3 × 3″ NaI(Tl) detector with digital spectrometer and GPS receiver, has been used to map dose rate and radionuclide activity concentrations before, after and at stages during this experiment. The data show the effect of the different stages of the experiment on dose rate at different locations around the site. The spectrometric data have allowed the assessment of the contributions of natural and anthropogenic radionuclides to the dose rate at different parts of the site before and after the experiment. This has clearly demonstrated the value of radiometric methods in evaluating remediation, and the effect of other environmental processes. The value of spectrometric methods which directly measure radionuclide concentrations has also been shown, especially through the identification of the contribution of natural and anthropogenic activity to the measured dose rate. The experiment has shown that clearing trees and applying wood chips can reduce dose rates by 10–15% beyond that achieved by just clearing the forest litter and natural redistribution of radiocaesium. Graphical abstract: Highlights: Evaluation of dose rate reduction at forest edges from clear felling and wood chip application. Measurements using portable gamma spectrometry system at stages during the experiment. Dose rate and radiocaesium activity concentrations measured. Dose rates reduced by 10–15%.